Comparison of single- and triple-dose contrast material in the MR screening of brain metastases. - Sze, G; Johnson, C; Kawamura, Y; Goldberg, S N; Lange, R; Friedland, R J; Wolf, R J (American Journal of Neuroradiology, 1998)
PURPOSE Although studies obtained with triple-dose contrast administration can show more brain metastases than those obtained with single-dose contrast material in patients with multiple metastases, such studies are costly and of limited clinical benefit. Since most patients who undergo screening have negative findings or a single metastasis, this study was performed to compare the clinical utility of single-dose versus triple-dose contrast administration in this large group of patients who could benefit from the possible increased sensitivity in lesion detection.METHODS Ninety-two consecutive patients with negative or equivocal findings or a solitary metastasis on single-dose contrast-enhanced MR images underwent triple-dose studies. Findings were compared with a standard of reference composed of panel review and long-term follow-up. Further analysis was performed by comparing results with those obtained by two blinded readers.RESULTS In all 70 negative single-dose studies, the triple-dose studies depicted no additional metastases in terms of the standard of reference. No statistically significant difference was seen between the results of the single- and triple-dose studies. For 10 equivocal single-dose studies, the triple-dose study helped clarify the presence or absence of metastases in 50% of the cases. In 12 patients with a solitary metastasis seen on the single-dose study, the triple-dose study depicted additional metastases in 25% of the cases. In the results of one of the two blinded readers, use of triple-dose contrast led to a statistical difference by decreasing the number of equivocal readings but at the expense of increasing the number of false-positive readings.CONCLUSION Routine triple-dose contrast administration in all cases of suspected brain metastasis is not helpful. On the basis of our investigation, we conclude that the use of triple-dose contrast material is beneficial in selected cases with equivocal findings or solitary metastasis, although with the disadvantage of increasing the number of false-positive results.